PENAFSIRAN KONTRAK DALAM PERSPEKTIF HERMENEUTIK - Mohammad Zamroni (Yuridika, 2016)
Ideally a contract does not need to be interpreted if the words used are be able to describe the parties' intentions. But as a proverb says, a word has a million of meanings. How good the words used in a contract, there is always ambiguity. So, in the implementation phase of the contract, the difference of interpretation often arises. Basically, contract law has provided guidance to the judges in interpreting the contract. The contract interpretation guidelines has been formulated in Article 1342 up to Article 1351 BW. But the principles of contract interpretation is generally used partially, so that interpretations often exacerbate differences of interpretation. Hermeneutics is a method which integrates all contract interpretation instruments. In terms of philosophists, hermeneutics is knowledge to comprehend an idea truthfully. The purpose of hermeneutics is to elaborate an idea clearly. By implementing the hermeneutics, the understanding to contract can be more comprehensive, not only the understanding to the text, but to the context, and the contextualization as well.